Feeding capability in the extinct giant Siamogale melilutra and comparative mandibular biomechanics of living Lutrinae. Issue 1 (December 2017) - Tseng, Z.; Su, Denise; Wang, Xiaoming; White, Stuart; Ji, Xueping
Abstract At 50 kg in estimated weight, the extinctSiamogale melilutra is larger than all living otters, and ranks among the largest fossil otters. The biomechanical capability ofS .melilutra jaws as related to their large size is unknown but crucial to reconstructing the species' potentially unique ecological niche. Here we compare the mandibular biomechanics ofS .melilutra using engineering-based performance measures against ten extant otter biomechanical models. Despite a wide range of feeding preferences from durophagy to piscivory, living otter species exhibit a linear relationship between mandible stiffness and volume, as expected in isometric model scaling. In contrast, S .melilutra models exhibit a six-fold increase in stiffness from expected stiffness-volume relationships calculated from extant species models. Unlike stiffness, mechanical efficiency of biting is conserved among living otters and inS .melilutra . These findings indicate that although similar to living bunodont otters in morphology and biting efficiency, jaw strength inS .melilutra far surpasses molluscivores such as sea otters and Cape clawless otters, even after accounting for size. Therefore, Siamogale represents a feeding ecomorphology with no living analog, and its giant size and high mandibular strength confer shell-crushing capability matched only by other extinct molluscivores such as the marine bearKolponomos .